Anisakis simplex complex (Nematoda: Anisakidae) in zooplankton communities from temperate NE Atlantic waters - Gregori, María; Roura, Álvaro; Abollo, Elvira; González, Ángel F.; Pascual, Santiago (Journal of Natural History, 2015)
19 páginas, 3 tablas, 3 figuras The euphausiid Nyctiphanes couchii and an unidentified mysid have been found, for the first time, with third-stage larvae (L 3 ) of the Anisakis simplex complex in the mesozooplanktonic community of the coastal upwelling system in Galicia (NW Spain). Parasite larvae were molecularly identified using the internal tran- scribed spacer (ITS) region. The prevalence of these parasites in the euphausiid population was 0.0019%. The existence of parasites in a variety of mesozooplank- ton organisms suggests that the transmission routes of A. simplex sensu stricto and A. pegrefii are wider than expected. The results suggest that these two Anisakis species are not specific to their intermediate hosts. Finally, the recruitment of A. simplex complex may be affected by oceanography, differing under upwelling or downwelling conditions. This research was supported by ‘ Canaries – Iberian Marine Ecosystem Exchanges ’ [grant number CTM-2007-66408-CO2-01] and ‘ Larval Ecology ’ [grant number CTM-2011-25929]. The first author and A.R. were funded by Junta para la Ampliación de Estudios pre-Doctorales (Spanish National Research Council) co-financed with Fondo Social Europeo (ESF) funds Peer reviewed